PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR BAHASA ARAB SISWA KELAS IX H DI SALAFIYAH WUSTHA ISLAMIC CENTRE BIN BAZ YOGYAKARTA - Widyaningtyas Kusuma Wardani; Retty Aurylia Kandea (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
This research is entitled "The Role of Teachers in Reminding the Interest in Learning Arabic of Class IX H Students at Salafiyah Wustha Islamic Centre Bin Baz Yogyakarta." This research was motivated when researchers made observations to students of the Islamic Center Bin Baz Salafiyah Wustha level, namely the lack of interest of students in learning Arabic. This study aims to determine the role of teachers in increasing students' interest in learning Arabic and to find out the obstacles faced by teachers in increasing students' interest in learning Arabic and to find out the picture of students' interest in learning Arabic.This research is a field research using qualitative data analysis with the research subject of class IX Arabic teacher H Salafiyah Wustha Islamic Center Bin Baz Yogyakarta with a total of 26 students. Data collection techniques use observation, interview and documentation methods. The results showed that the role of teachers in increasing students' interest in learning Arabic with teachers acting as teachers, guides, class managers, motivators and second parents at school. The obstacles faced by teachers in increasing students' interest in learning Arabic are, different student backgrounds, lack of cohesion among teachers, the existence of Arabic teachers who are accustomed to using Indonesian, students are accustomed to the tarjamah method and memorization methods, students are not accustomed to using Arabic in daily life, students lack concentration and lack interest in participating in teaching and learning activities, Students do not respond when asked, the social environment of students and students do not have a goal in learning Arabic. Based on the results of interviews with students, the picture of students' interest in learning language states that students like Arabic and are familiar with Arabic.